The relation between brewed tea and drinking water with urinary fluoride concentration among youths - Izanloo, Hassan; Asadi-Ghalhari, Mahdi; Mohebi, Siamak; Hasanpoor, Fatemeh; Hozoori, Mohammad (Progress in Nutrition, 2019)
Background: Fluoride is an element that enters the body from different dietary and non-dietary sources. Water and brewed tea are the main dietary sources of this element. Therefore, we are going to assess the student’s urinary fluoride concentration and evaluated whether there is a relation between the amount of drinking water and tea with urine.Methods: In a cross-sectional study, we enrolled 100 males and female students of Qom University of Medical Sciences. Daily intake of water and brewed tea were assessed in three days before obtaining urine samples. Urinary fluoride concentration tested in samples by using of spectrophotometer model DR-4000 and in the method of SPADNS. Results: Fluoride levels in the urine of male and female students were almost similar and it was about 1.45 mg/lit. There was a significant relation between urinary fluoride concentration and the number of consumed cups of tea (P<0.01). There was no difference between male and female students. Conclusion: Based on the findings of this study, it seems that the tea-drinking habit was correlated with higher urinary fluoride concentration. In community-based nutrition education, perhaps we should consider more tea-drinking-related factors when we suggest tea consumption.